An evaluation of the current practices followed by oncologists in private practice in Cape Town, South Africa, in the management of patients with advanced cancer which no longer responds to anticancer treatment and the identification of the needs associated with such management - Grove, Jan (Department of Public Health and Family Medicine, 2015)
Includes abstract.~Includes bibliographical references.